2017
DOI: 10.1039/c7nr02798b
|View full text |Cite
|
Sign up to set email alerts
|

Indocyanine green-loaded gold nanostars for sensitive SERS imaging and subcellular monitoring of photothermal therapy

Abstract: We have demonstrated that a typical nanothermometer was incorporated in a bovine serum albumin stabilized gold nanostar-indocyanine green (denoted as GNS-ICG-BSA) nanoprobe to realize surface-enhanced Raman scattering (SERS) imaging-based real-time sensitive monitoring of intracellular temperature in photothermal therapy (PTT), which significantly improved the spatial resolution compared to infrared thermal imaging. Herein, an exogenous thermosensitive molecule, ICG, acting as a tri-functional agent, was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 73 publications
1
34
0
Order By: Relevance
“…J-aggregated ICG molecules or conjugation to plasmonic nanoparticles are shown to enhance ICG photostability. [51][52][53] The photodegradation properties of ICG are also cleverly utilized for drug delivery strategies as reviewed recently by Gorka and Schnermann. 51 Furthermore, ICG was shown to have enhanced photostability via encapsulation in lipids or association with plasmonic gold colloids.…”
Section: Photoacoustic Monitoring Of Indocyanine Green Photodegradatimentioning
confidence: 99%
“…J-aggregated ICG molecules or conjugation to plasmonic nanoparticles are shown to enhance ICG photostability. [51][52][53] The photodegradation properties of ICG are also cleverly utilized for drug delivery strategies as reviewed recently by Gorka and Schnermann. 51 Furthermore, ICG was shown to have enhanced photostability via encapsulation in lipids or association with plasmonic gold colloids.…”
Section: Photoacoustic Monitoring Of Indocyanine Green Photodegradatimentioning
confidence: 99%
“…This demonstrates that HSA-ICG-MB NPs are efficient photothermal transducers to produce significant hyperthermia (>42 o C). 52 During photothermal heating, the ICG molecules in NPs gradually decompose 53 , 54 , and their FRET efficiency accordingly decreases, resulting in changes in the fluorescence and PA signals of the donor-acceptor pair. It was observed that with increasing temperature, the fluorescence intensity of ICG (centered at 810 nm) decreased, while MB emission (centered at 685 nm) enhanced correspondingly (Figure 2 c).…”
Section: Resultsmentioning
confidence: 99%
“…During the process, the fluorescence signal from MB gradually rose, and the fluorescence emission from ICG decreased monotonically with prolonged irradiation time from 0 to 5 min (Figure 3 b). These changes stem from photothermal decomposition of ICG in NPs, 54 decreasing the FRET efficiency. Therefore, FRET-based dual-channel fluorescence imaging can be applied for clear visualization of the cellular therapeutic responses.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleic acid sequences extracted from clinical samples were amplified before SERS detection. For instance, RNA was extracted from the urine of prostate cancer patients and amplified using multiplex reverse transcription recombinase polymerase amplification . Discrimination among healthy and cancer patients was attained using principal component analysis linear discriminant analysis (PCA‐LDA) analysis with sensitivity and specificity of 89.1% and 95.6% for colorectal cancer and 100% and 94.1% for gastric cancer.…”
Section: In Vitro Detection Of Biomarkers With Sers For Cancer Diagnomentioning
confidence: 99%